(untitled) (South Asian Journal of Agriculture, 2019)
The main purpose of the study was to identify the training needs of the teachers of Khulna University. Data were collected from randomly selected 54 teachers out of 280 through mailed questionnaire (Both hard and email copy) during June to July, 2010. To identify level of knowledge and training needs of the respondents 20 items/ issues under 5 broad areas (viz. teaching methodology, research methodology, computer skill, office management & administration and extension & outreach) were selected. To determine the level of knowledge a 5- points rating scale such as little knowledge, some knowledge, substantial knowledge, high knowledge and very high knowledge were used and a score of 1, 2, 3, 4 and 5 were assigned against the scales respectively. To determine the training need a 5- points rating scale such as little need, some need, substantial need, urgent need and very urgent need were employed and a score of 1, 2, 3, 4 and 5 were assigned against the scales respectively. To identify the issues and areas of knowledge and training, knowledge index and training need index were calculated respectively. The respondents had highest level of knowledge in teaching methodology, while it was least in case of extension and outreach among the five selected broad categories. The respondents expressed very urgent training needs in extension and outreach and least training needs in teaching methodology. The respondent teachers also identified top five issues on which they want to take training are conflict management (under extension and outreach), budget preparation (office management and administration) acquaintance with field problem (extension and outreach), research design and project preparation (research methodology), and data analysis and management (computer skill). Among age, professional experience, educational qualification training experience and level of knowledge, only level of knowledge showed a negative significant relationship with the training need of the respondents. South Asian J. Agric., 7(1&2): 44-50